PENGARUH KOMISARIS INDEPENDEN, RISK MANAGEMENT COMMITTEE DAN KONSENTRASI KEPEMILIKAN TERHADAP PENGUNGKAPAN MANAJEMEN RISIKO DAN DAMPAKNYA PADA NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2014-2016) - Claudia, Rahayu Aisyah; Novita, Indrawati; Al, L Azhar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to examine the direct influence of independent commissioners, riskmanagement committee and ownership concentration on firm value, and indirect testingof independent commissioners, risk management committee and ownership concentrationon firm value through mediating variables, namely risk management disclosures. Sampleswere taken using Purposive sampling method. The total population is 144 and the sampleis 109 manufacturing companies listed on the Indonesia Stock Exchange in 2014-2016.The method used in this study is a descriptive varificative method using secondary dataobtained from annual reports and company financial statements. Hypothesismeasurement using path analysis with PLS (Partial Least Squere) software. The results ofthe study show that the direct influence: (1) independent commissioners, concentration ofownership and disclosure of risk management influence the value of the company, whilethe risk management committee does not affect the value of the company. (2) ownershipconcentration affects risk disclosure disclosure, while independent commissioners andrisk management committees have no effect on risk management disclosures. For indirecteffects, it shows that independent commissioners, risk management committees andownership concentration do not affect the value of the company through risk managementdisclosures.Keywords : Corporate Value, Risk Management Disclosure, IndependentCommissioner, Risk Management Committee and Concentration ofOwnership